2015
DOI: 10.1021/acsami.5b01878
|View full text |Cite
|
Sign up to set email alerts
|

Non-Faradaic Electrical Impedimetric Investigation of the Interfacial Effects of Neuronal Cell Growth and Differentiation on Silicon Nanowire Transistors

Abstract: Silicon nanowire field-effect transistor (SiNW FET) devices have been interfaced with cells; however, their application for noninvasive, real-time monitoring of interfacial effects during cell growth and differentiation on SiNW has not been fully explored. Here, we cultured rat adrenal pheochromocytoma (PC12) cells, a type of neural progenitor cell, directly on SiNW FET devices to monitor cell adhesion during growth and morphological changes during neuronal differentiation for a period of 5-7 d. Monitoring was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…The real-time measurements show signal change when hypoxia is generated, and a comparison for different oxygen concentrations, including absence of signal change when Ca 2+ channels are blocked with cadmium ions. [5] Copyright 2015, ACS Publications, https://pubs.acs.org/ doi/10.1021/acsami.5b01878, further permissions related to this figure should be directed to ACS. [171] Copyright 2013, ACS Publications.…”
Section: Alternative Measurement Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…The real-time measurements show signal change when hypoxia is generated, and a comparison for different oxygen concentrations, including absence of signal change when Ca 2+ channels are blocked with cadmium ions. [5] Copyright 2015, ACS Publications, https://pubs.acs.org/ doi/10.1021/acsami.5b01878, further permissions related to this figure should be directed to ACS. [171] Copyright 2013, ACS Publications.…”
Section: Alternative Measurement Modesmentioning
confidence: 99%
“…Biotin binding on a streptavidin layer above the Debye length in 100 × 10 −3 m ionic strength buffer could be sensed. Impedance technique was also used for cell analysis by Lin et al [5] (Figure 11c). As pointed out by Ingebrandt, [184] the use of this technique with nanoscale sensors might be of a significant impact for biosensing (Figure 11b).…”
Section: Alternative Measurement Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the impedance of a non-faradaic sensor arises from the effect caused by the insulating characteristics of the target analyte bond to the conductive substrate. 13 Typically, the most valuable impedance parameter in this case is the double layer capacitance and it is only limited by the nature of the charge carriers and their concentration in the boundary layer of the transducer substrate. 3 Nonetheless, the |Z| and φ components are adequate transducer parameters.…”
Section: Non-faradaic Sensorsmentioning
confidence: 99%
“…Lin et al reported on an electric cell-substrate impedance sensing (ECIS) system with field effect transistor (SiNW FET) to detect the differentiation of PC12 cells on silicon nanowire electrodes in real-time [ 40 ]. They monitored cell morphology and growth during neuronal differentiation for 5 to 7 days using a SiNW-coated FET device through E4980A precision LCR meter (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Electrochemical and Electrical Detection System To Monitomentioning
confidence: 99%